The Interesting Teaching and Learning of Malay Language to Foreign Speakers: Language through Cultures - Baharudin, Mazlina; Ikhsan, Siti Ajar (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2016)
The interesting teaching and learning of Malay languages is a challenging effort and need a relevant plan to the students’ needs especially for the foreign students who already have the basic Indonesian Malay language variation that they have learned for four semesters in their own country, Germany. Therefore, the variety of teaching and learning strategies should be considered by the teachers to make teaching and learning become interesting, effective and not boring. Basic effectiveness of a language program was the factors of socio-culture, the style of teaching and learning, the students, and the characteristics of the program. This paper however focused on the socio-cultural factors (learning of cultures) and the activities program that enable to generate excitement and effectiveness in the teaching and learning of Malay language as a foreign language. In the teaching and learning process found that the more we gave the activities to the students, the more the students acquired the meaning of the lessons. In this study, the selected respondents were the two groups of students from TWG, Konstanz, Germany who have followed the Malay Language and Culture Program in the Languages, Literacies and Translation Center, University of Sains Malaysia, Penang, in 2011. The first group was started in March to June, and the second group in September to November. The research was based on formal and informal observations and interviews. This paper also discussed about the outdoor activities program used as curriculum in the teaching and learning process that gives an interesting environment to foreign students